Spiritual Values in the Novel Aerospace Dan Homecoming by Jaquenza Eden: Sociological Study of Literature - Sari, Yusmita; Nasution, Ikhwanuddin; Marsella, Emma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of this research is to describe the spiritual values found in Jaquenza Eden's novel Dirgantara and Keulangan using a literary sociology approach. Where, spiritual values according to Notonegoro (in Setiadi and Usman, 2011: 125) are divided into four, namely truth values, beauty values, aesthetic values and religious values. This research uses a qualitative descriptive method with the main object data sources, namely the Novel Dirgantara and Homecoming by Jaquenza Eden. The data collection technique used in this research is using library study techniques with the application of heuristic methods. Based on the research results, it was found that there are many types of spiritual values contained in the novel Dirgantara and Kepulangan by Jaquenza Eden. The truth value in this research is divided into two parts, namely absolute truth and relative truth. Beauty Value, which originates from the element of feeling. Beauty value in this research is divided into two parts, namely authentic beauty and natural beauty. Moral Values, which originate from the element of will, especially in human behavior between assessing actions that are considered good or bad, noble or despicable according to the order that applies within that social group. In this case, moral values are divided into the values of awareness, patience,regret for working hard, apologizing, longing, joking, filial piety, mutual help, responsibility, gratitude, compassion, sharing and caring. Religious values are absolute values based on those established by religion, God and the holy books.